Informed Consent and Clinical Trials - A Jewish Perspective - Heyd, David (Studia Bioethica, 2019)
Clinical trials started no more than 150 years ago. Informed consent is an even more recent moral principle in medical practice. It is accordingly no surprise that the Jewish tradition (like all other religious and ethical systems) consists of no direct instruction on these practices. This, however, does not mean that the two-and-half millennia old corpus of Jewish law is completely silent on the principles which may guide us in modern times in the regulation of experiments on human subjects and the role of individual consent on part of those participating in them.